1/f Noise and Machine Intelligence in a Nonlinear Dopant Atom Network. Issue 3 (15th March 2021) - Chen, Tao; Bobbert, Peter A.; van der Wiel, Wilfred G.
Abstract : 1/ f Noise and Machine Intelligence Intrinsic material properties can be exploited to realise highly efficient unconventional computing. In article number 2000014, Wilfred G. van der Wiel and co‐workers present the concomitance of 1/ f noise and machine intelligence in a dopant atom network and draw the analogy with the human brain. It is suggested that the observed conditions for optimal information processing can potentially be generalized to other complex nonlinear physical systems.